Pengembangan Media Busy Book Pada Materi Sistem Pencernaan Hewan Ruminansia Kelas V Sekolah Dasar - Dini Puspita Ramandanni; Nataria Wahyuning Subayani; Iqnatia Alfiansyah (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This study aims to develop Busy Book learning media on the material of the digestive system of ruminants for grade V elementary school. This research is a development research using the ADDIE model which consists of five stages (analysis, design, development, implementation, evaluation). The subject of this study consisted of 25 students. The results of the research that has been carried out show that the Busy Book media on the material for the digestive system of ruminants for class V elementary school fulfills the validity indicators, namely a) the results of validation from the material expert validator obtain a score of 95%, material expert 2 obtains a score of 92.5% while media expert 1 get a score of 85%, media experts 2 get a score of 95% with a very valid category. b) the response from the students obtained a percentage of 86.2% in the very good category. c) the learning outcomes of students obtain a percentage of 84% with complete criteria. based on this description, the learning media and material contained in the media developed by researchers can be used in the learning process.